Study on the Fourth Industrial Revolution (IR 4.0) Implementation for Improving IBS Construction Project - Kamil, Nurul Ain Qadrina; Kasim, Narimah; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun; Ang, Peniel Soon Ern (Research in Management of Technology and Business, 2023)
The Fourth Industrial Revolution (IR 4.0) is a digital revolution that refers to a process of technical progress in construction industry and is still not properly addressed. Industrial Building System (IBS) is one of the most effective methods of improving quality and efficiency in a building project. However, there are many contractors who are still comfortable with the traditional method application with the assistance of unskilled labour for project activities. Thus, the objectives of this study were conducted to identify the potentials, influencing factors, and steps to promote the Fourth Industrial Revolution (IR 4.0) implementation for improving Industrial Building System (IBS) construction project. To achieve the objectives, the research had been conducted using quantitative method for primary data collection and questionnaires as the instrument that was used to collect the data. There were 146 respondents out of 346 respondents among G7 contractors were selected at Selangor state to obtain information for this research. The respondents for this research are 146 respondents from G7 contractors in the state of Selangor. Then, the data analysed by using Statistical Package of Social Science (SPSS) were determined by frequency analysis, percentage, standard deviation, and mean score values. Furthermore, pie charts, frequency, and percentage values for the respondents’ backgrounds. The results showed that IR 4.0 implementation had the potential to improve IBS installation skills need a workforce capable of producing and installing building components either on-site or off-site. The influencing factors of the IR 4.0 implementation had to upgrade complex machinery to produce quality IBS components. In conclusion, the steps to promote the IR 4.0 implementation had to promote high-quality machine with IR 4.0 implementation for the IBS component assembly process.